PENGUJIAN FENOMENA EFEK SENIN (MONDAY EFFECT) DAN WEEKFOUR EFFECTDI BURSA EFEK INDONESIA - Alvia, Liza; Silaban, Delia Tika (Universitas Muhammadiyah Magelang, 2009)
The objective of this research is to reexamine the anomaly of Monday effect and week four effect at Indonesian Stock Exchange (ISE). Using Jakarta Composite Index from 2003 until 2007 and ANOVA to answer the research questions. The results of this research show that there was no difference return between Monday and Tuesday until Friday. The first hypothesis said that Monday return would be lower than another day return was rejected. And also for the second hypothesis, Monday return would be lower on week four was rejected. It means that Monday effect and week four effect was not happen on Indonesian Stock Exchange.